On the best L_1-approximation of truncated powers by algebraic polynomials - Nitiema, P. K. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We determine the asymptotic behavior of the best L_1-approximations of the kernels (x - a) + r - 1, 1 < r < 2, and the classes W_1^r by algebraic polynomials.